Design and Study of an mmWave Wearable Textile Based Compact Antenna for Healthcare Applications. (20th December 2021) - Monirujjaman Khan, Mohammad; Hossain, Junayed; Islam, Kaisarul; Ovi, Nazmus Sadat; Shovon, Md. Nakib Alalm; Abbasi, Muhammad Inam; Bourouis, Sami
Abstract : In this study, the design of a compact and novel millimeter wave cotton textile-based wearable antenna for body-centric communications in healthcare applications is presented. The free space and on-body antenna performance parameters for the proposed antenna at 60 GHz are investigated and analyzed. The antenna is based on a 1.5 mm thick cotton substrate and has an overall dimension of 7.0 × 4.5 × 1.5 mm 3 . In free space, the antenna is resonant at 60 GHz and achieves a wide impedance bandwidth. The maximum gain at this resonant frequency is 6.74 dBi, and the radiation efficiency is 93.30%. Parametric changes were carried out to study the changes in the resonant frequency, gain, and radiation efficiency. For body-centric communications, the antenna was simulated at 5 different distances from a three-layer human torso-equivalent phantom. The radiation efficiency dropped by 24% and gradually increased with the gap distance. The antenna design was also analyzed by using 10 different textile substrates for both free space and on-body scenarios. The major benefits of the antenna are discussed as follows. Compared to a previous work, the antenna is very efficient, compact, and has a wide bandwidth. In BCWCs for e-health applications, the antenna needs to be very compact due to the longer battery life, and it has to have a wide bandwidth for high data rate communication. Since the antenna will be wearable with a sensor system, the shape of the antenna needs to be planar, and it is better to design the antenna on a textile substrate for integration into clothes. The antenna also needs to show high gain and efficiency for power-efficient communication. This proposed antenna meets all these criteria, and hence, it will be a good candidate for BCWCs in e-health applications.